1849 Cal. Stat. 245 - (:unkn) unknown (My University, 1849)
An Act to Incorporate the City of San Francisco, § 127: Prohibited the carrying, with intent to assault any person, any pistol, gun, knife, dirk, bludgeon, or other offensive weapon with the intent to assault another person.. Punished by fine of up to $100 and imprisonment for up to 3 months.
Keywords: CARRY - INTENT TO COMMIT CRIME